2011
DOI: 10.1590/s0100-40422011000500021
|View full text |Cite
|
Sign up to set email alerts
|

Electrocatalysis in wastewater treatment: recent mechanism advances

Abstract: Recebido em 23/9/10; aceito em 4/12/10; publicado na web em 25/3/11Over 50 years, several scientists and industries have developed new alternatives for wastewater treatment and remediation. Recently, electrochemical technology has been largely developed mainly because of its versatility and environmental compatibility. Scientific contributions about role of the electrode material have allowed determining that the influence of material in the selectivity is an important parameter. However, to interpret this beh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
57
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 113 publications
(60 citation statements)
references
References 29 publications
(62 reference statements)
2
57
0
1
Order By: Relevance
“…Comninellis and Chen [10] indicated that the nature and amount of intermediates formed during electrochemical mineralization of organic compounds at BDD anodes depends on the process conditions. In the literature, it was reported that the main intermediates were aliphatic compounds such as oxalic and maleic acids which may undergo further anodic oxidation at a much lower rate [10,22,36,37]. Therefore, in our previous study [9], a novel parameter was defined in Eq.…”
Section: Resultsmentioning
confidence: 99%
“…Comninellis and Chen [10] indicated that the nature and amount of intermediates formed during electrochemical mineralization of organic compounds at BDD anodes depends on the process conditions. In the literature, it was reported that the main intermediates were aliphatic compounds such as oxalic and maleic acids which may undergo further anodic oxidation at a much lower rate [10,22,36,37]. Therefore, in our previous study [9], a novel parameter was defined in Eq.…”
Section: Resultsmentioning
confidence: 99%
“…Canizares는 전기화학 반응기를 음극과 양극 반응 영역 그리고 간접산화가 일어나는 벌크영역 3가지 영역으로 나누어 모델링을 진행하였으며 [13], Mascia는 BDD 전극에서의 hydroxyl radical과 유기물 확산에 의한 산화반응 모델링을 연구하 였다 [14]. (1), (2), (3)에 나타내었다 [18]. …”
Section: 유기물 양극산화에 대한 수학적 모델링 연구는 가장 먼저 Comninellisunclassified
“…[23] However, when the aim is to eliminate organic load, color and odor, a limiting factor is that organic compounds cannot be destroyed (mineralized) by this method alone, thus requiring the use of additional treatments. [40,41] During this process, the organic matter in solution diffuses from the bulk solution to the electrode/ solution interface, where it is transformed into CO 2 and H 2 O. [31] These methods are characterized by their generation of hydroxyl radicals ( * OH), which can mineralize highly recalcitrant compounds.…”
Section: Introductionmentioning
confidence: 99%